Seismic vulnerability of state educational infrastructures in Cercado de Lima, using the FEMA 154 methodology - Calixto, Valerie (2023)
Peru is a country with high seismic vulnerability due to its location in the Pacific Ring of Fire, an area of significant seismic activity. In this regard, although the Peruvian government has a disaster risk management plan in place, it is crucial to contribute to and identify those critical infrastructures (schools, hospitals, police and fire stations, emergency control centers, etc.) with a higher degree of seismic vulnerability. After their identification, a structural reinforcement plan can be implemented for these structures. For this reason, the study presents public schools with the highest degree of seismic vulnerability in Cercado de Lima, Lima, Peru. These were identified using the FEMA P-154 Rapid Visual Screening methodology, which focuses on quickly and economically assessing the seismic safety of a large inventory of buildings with minimal data requirements. Upon concluding the research, the results indicate that over 60% of public institutions in Cercado de Lima have a high probability of suffering significant damage in an earthquake.